2013
DOI: 10.1016/j.jtbi.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian multivariate Poisson abundance models for T-cell receptor data

Abstract: A major feature of an adaptive immune system is its ability to generate B- and T-cell clones capable of recognizing and neutralizing specific antigens. These clones recognize antigens with the help of the surface molecules, called antigen receptors, acquired individually during the clonal development process. In order to ensure a response to a broad range of antigens, the number of different receptor molecules is extremely large, resulting in a huge clonal diversity of both B- and T-cell receptor populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Finally, the many-replicate experimental design employed in this study, in which each of the 188 PCR wells corresponds to a replicate sample, constitutes a sample abundance probe robust to the inherent stochasticity of PCR amplification. Moreover, this approach represents a crucial quantitative advance over previous sequencing studies of antigen receptor repertoire diversity, which have been limited by either poor quantitation or by the lower throughput of single-cell methods[ 27 , 62 , 63 ]. We expect that these data will be used by other experts in the field of immunology to address additional fundamental questions about BCR development and in vivo antigen binding in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the many-replicate experimental design employed in this study, in which each of the 188 PCR wells corresponds to a replicate sample, constitutes a sample abundance probe robust to the inherent stochasticity of PCR amplification. Moreover, this approach represents a crucial quantitative advance over previous sequencing studies of antigen receptor repertoire diversity, which have been limited by either poor quantitation or by the lower throughput of single-cell methods[ 27 , 62 , 63 ]. We expect that these data will be used by other experts in the field of immunology to address additional fundamental questions about BCR development and in vivo antigen binding in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Because the size of a sample is dwarfed by the size of the total population (and therefore sampling does not drastically alter clonotype relative abundances), these authors approximated the multivariate hypergeometric distribution using a Poisson distribution. Incorporation of a varying sampling rate for clonotypes of varying frequencies leads to the class of PAMs [ 41 , 82 ]. They applied their method to previously published data on mice with different phenotypes, and evaluated the consistency of their method by excluding clonotypes above successively higher cut-off frequencies.…”
Section: Parametric Species Richness Estimatorsmentioning
confidence: 99%
“…Rempala et al [ 41 ] focused on one such model, the bivariate Poisson-lognormal distribution, and concluded that under-sampling in their repertoire datasets is more severe (and thus the population is more diverse) than would be estimated using the Good-Turing estimator [ 77 ]. Other extensions of the class of PAMs have been developed [ 41 , 82 ] that estimate the similarity between populations in the presence of unseen clonotypes.…”
Section: Parametric Species Richness Estimatorsmentioning
confidence: 99%
“…This approach can overcome the substantial sampling fluctuations derived from the huge diversity in TCR repertoires and provides a stable result related to the inter-sample distances on the basis of statistical interpretations. Variations of PA models have also been proposed ( 8 10 ), and methods to combine both approaches were also developed recently. For example, Rempala et al ( 11 ) used a bivariate Poisson log-normal (BPLN) distribution to model joint abundance distributions for classifying eight different samples of the following sample conditions: donor sites, types of T cells, and the genetic backgrounds of different mouse lines.…”
Section: Introductionmentioning
confidence: 99%